Hydroelectric sprinkler / Ahmad Syukri Abdul Aziz, Ahmad Alif Qadri Mohd and Ahmad Syahmi Mohamad - Abdul Aziz, Ahmad Syukri; Mohd, Ahmad Alif Qadri; Mohamad, Ahmad Syahmi (2015)
The main purpose of this Hydroelectric Sprinkler project is to use a renewable energy and apply it to water sprinkler devices. The renewable energy that used in this project is hydroelectric. Hydroelectric is a kind of renewable energy that created by flowing water which rotates the fan or turbine thus producing kinetic energy and electricity. The fan or turbine operated on a simple principle which is when there is water flowing, the water flow will push the fan or turbine and make it rotate. In order to produce the electricity energy, the generator is connected to two series connected DC motor to produce voltage, and then the produce voltages are used to charge a battery. A gear motor is connected to the control circuit as a main output in this project. The charged battery is used as the supply for the control circuit. Then sprinkler is used as an output device. The water sprinkler is ON when the light intensity from the sun is radiated to the sensor and OFF when there are no light.